Determining Hardening Soil Model Parameters of Urmia Lake Sand by Numerical Modeling of Undrained Triaxial Test and Comparison with Laboratory Results - Hadi Bahadori; Vahid Mohammadi (مجله مدل سازی در مهندسی)
Triaxial soil test is one of the most important and widely used experiments to identify the soil behavior and determination of soil shear strength parameters. Thorough study of the soil behavior requires numerous experiments that require time and cost. The alternative solution is the use of numerical modeling. Numerical modeling requires constitutive soil model to provide a qualitative description of soil behavior using behavioral parameters and provide the relationship between stress-strain in different states and under different loads. In this research, numerical modeling undrained triaxial test with finite element method by Midas GTS NX software under different confining pressures have been done. Validation of the numerical modeling has been done with the data available in the technical literature. The hardening soil model shows the most agreement with the stress-strain behavior of the soil compared to the conventional Mohr-Coulomb model. Therefore, better results can be observed in geotechnical engineering modeling by having hardening soil model parameters. Therefore, in this paper, the behavioral parameters of the hardening soil for the standard Urmia lake sand are determined using repeated numerical modeling using the finite element method and compared with the laboratory results. The matching between these results demonstrates the ability of the present modeling method to determining the required behavioral parameters of all types of soils.